Assessing the Individual Interviewer Rapport-Building and Supportive Techniques of the R-NICHD Protocol - Tamm, Anett; Otzipka, Jana; Volbert, Renate (Frontiers in Psychology, 2021)
The use of the rapport-building and supportive techniques formulated by the R-NICHD protocol is intended to support children and increase the quality of their statements as well as disclosures without possessing suggestive potential. While the effectiveness of the entire R-NICHD protocol for children who have actually experienced child sexual abuse (CSA) has been supported by research, to date no study assessed the effect of each individual socio-emotional interview technique in both interviewees with and without CSA experiences. The current study aimed to address this gap in research by means of an online vignette-study, asking participants to rate the identified rapport-building and supportive techniques on the scales well-being, willingness to talk and perceived pressure. A total of 187 participants were randomly assigned to either an “abused” or a “not abused” group by means of a vignette-manipulation. The results suggest that many socio-emotional interview techniques were perceived as supportive and non-suggestive whilst a number of techniques were perceived as not supportive but suggestive. Few differences emerged between the “abused” group and the “not abused” control group. To conclude, most but not all rapport-building and supportive techniques proposed by the R-NICHD protocol had a positive effect on interviewees. Future research should focus on the effects of individual techniques instead of global effects of the entire R-NICHD protocol.